2016
DOI: 10.1111/sltb.12248
|View full text |Cite
|
Sign up to set email alerts
|

Is Cumulative Exposure to Suicide Attempts and Deaths a Risk Factor for Suicidal Behavior Among Firefighters? A Preliminary Study

Abstract: The present study examined the association between cumulative exposure to suicide attempts and deaths and suicidal behavior in a sample of 61 professional firefighters. On average, firefighters reported 13.1 (SD=16.6) exposures over the course of their lifetime. Cumulative exposure to suicide attempts and deaths was positively correlated with suicidal behavior (r = 0.38, p = 0.004). Moreover, firefighters with 12+ exposures were more likely to screen positive for risk of suicidal behavior (OR = 7.885, p = 0.02… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
52
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 18 publications
1
52
0
Order By: Relevance
“…Although the vast majority of individuals exposed to traumatic events do not go on to develop PTSD [50], the repeated traumatic exposures inherent in firefighting may serve to enhance the exacerbation of pre-existing vulnerabilities for both PTSD and suicidality, such as AS [51]. Thus, regarding firefighters, it is possible that the distress conferred by repeated occupational exposures (e.g., house fires, medical emergencies, suicide deaths of others; [52,53]) may increase levels of AS. This increase, in turn, may serve to amplify the effects of AS on depression symptoms (which themselves overlap, in part, with PTSD symptoms; [54]) in the prediction of suicide risk, consistent with the propositions of the depression-distress amplification model.…”
Section: Discussionmentioning
confidence: 99%
“…Although the vast majority of individuals exposed to traumatic events do not go on to develop PTSD [50], the repeated traumatic exposures inherent in firefighting may serve to enhance the exacerbation of pre-existing vulnerabilities for both PTSD and suicidality, such as AS [51]. Thus, regarding firefighters, it is possible that the distress conferred by repeated occupational exposures (e.g., house fires, medical emergencies, suicide deaths of others; [52,53]) may increase levels of AS. This increase, in turn, may serve to amplify the effects of AS on depression symptoms (which themselves overlap, in part, with PTSD symptoms; [54]) in the prediction of suicide risk, consistent with the propositions of the depression-distress amplification model.…”
Section: Discussionmentioning
confidence: 99%
“…LEOs are routinely exposed to trauma in a myriad of ways, including the witnessing of the aftermath of interpersonal violence, motor vehicle accidents, child abuse, the possibility of having to be the initiator of violence in life-threatening situations, such as an officer-related shooting, as well as homicide and suicide. One study confirmed that most police officers (76%) are exposed to major traumatic events other than suicide, with one third reporting the trauma exposure was personally traumatic for them (Heffren & Hausdorf, 2014). LEOs acknowledge the importance of trauma on their colleagues, with one study finding over half of the participants having personally known LEO who "changed" after experiencing a traumatic event (Fleischmann, Strode, Broussard, & Compton, 2016).…”
mentioning
confidence: 99%
“…First, firefighters experience a high degree of exposure to suicide by virtue of their vocational responsibilities (i.e. responding to suicide deaths; Kimbrel et al, 2016). Second, firefighters represent an occupational group at elevated risk for suicide (Stanley, Hom, & Joiner, 2016;Stanley, Hom, Hagan, & Joiner, 2015;Stanley, Hom, Spencer-Thomas, & Joiner, 2017).…”
mentioning
confidence: 99%
“…One notable limitation of this study is its lack of assessment of degree of closeness to the deceased. Building on this study, Kimbrel et al (2016) examined 61 firefighters, all of whom reported exposure to suicide and found that the cumulative suicide exposure was associated with higher suicide risk levels. However, contrary to expectations, they did not find that perceived closeness to decedents was significantly related to suicide risk levels.…”
mentioning
confidence: 99%